MENSTRUATION AT WORK SHOULD NOT BE A PROBLEM – PERIOD! - Petrović, Mila D (Pravni zapisi, 2025)
Even though menstruation is a normal part of female biology, it still represents a taboo, a source of stigma, prejudice and practices that create further rifts in already heavily divided society. Not only is such a situation unjust and offensive, but it also creates problems in the work environment. The mere fact that a woman is menstruating puts her at risk of being perceived as incompetent, creates potential hygienic and logistical issues, and, in certain cases, fairly aggravates the possibility of female employees performing at work. Such a situation calls for policies that can accommodate the needs of menstruating employees, as well as for their protection from any unwanted behavior that could weaponize an individual’s innate biological feature. Hence, the purpose of this paper is to analyze the position of menstruating employees at work, as well as possible policies that can be introduced by the employer in order to facilitate their position.